2000
DOI: 10.1159/000063432
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment and Serum Hormonal Profile in Prepubertal Hypertrichosis

Abstract: Twenty-two prepubertal girls with hypertrichosis were studied and compared to 10 prepubertal normal girls. Hypertrichosis was assessed according to a score that considers the amount and the distribution of vellus hair in androgen- and non-androgen-sensitive areas. Serum androgen profile and free androgen index (FAI) were determined in both groups. The hypertrichosis score was higher in patients than in the normal girls. Testosterone levels and FAI were increased in patients when compared to control; 3α-androst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Gryngarten et al observed increased serum testosterone levels and FAI in a group of prepubertal girls with hypertricosis compared to controls. In addition, they observed a slight increase in 3α-androstanediol glucuronide concentrations in approximately half of their girls with hypertrichosis [13]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gryngarten et al observed increased serum testosterone levels and FAI in a group of prepubertal girls with hypertricosis compared to controls. In addition, they observed a slight increase in 3α-androstanediol glucuronide concentrations in approximately half of their girls with hypertrichosis [13]. …”
Section: Discussionmentioning
confidence: 99%
“…The patients and control girls underwent a careful physical examination performed by a single pediatric endocrinologist (MIH), to determine their hypertrichosis score according to Gryngarten et al [13]. As indicated by this author, a score above 7 was considered positive for hypertrichosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertrichosis is a frequent finding in prepubertal girls, and differs from hirsutism in the quality of the hair, and in its anatomic distribution in androgen and non-androgen-dependent sensitive areas. A study performed in Latin American girls suggests that hypertrichosis may be secondary to a slight increase in total testosterone, and an increase in peripheral 5α-reductase activity (21).…”
Section: Hiperandrogenism (Ha)mentioning
confidence: 99%